The Relationship between Exemplary Leadership of Head Nurse and Nurse Job-Satisfaction in Lower Northern Regiinal Hospital under ministry of Public Health - Phichitsiri, Suphatthra; Pongrangsarn, Phattharamanat (NU Journal of Nursing and Health Sciences, 2020)
This cross-sectionalsurvey research aimed to 1) examine level of exemplary leadership of head nurses 2) examine level of nurses job-satisfaction and 3) identify relationship between exemplary leadership of head nurses and nurse job-satisfaction. Participants were 335 nurses working in regional hospital located in lower northern region. The research instrumentwas a questionnaire consisted of exemplary leadership of head nurse and nurse job-satisfaction. The Index of Item - Objective Congruence (IOC) of the questionnaire was examined by experts. Cronbach alpha coefficient was tested which were 0.92 and 0.88 respectively. The data were analyzed by using frequency, mean, standard deviation, and Pearson’s Product Moment Correlation coefficient. Findingwere as follow 1) the exemplary leadership level of the head nurses was at high level ( = 4.12 S.D. = 0.52) 2) the level of nurses job-satisfaction was at high level ( = 4.00, S.D = 0.51) and 3) the relationship between exemplary leadership of head nurses and nurse job-satisfaction showed statistically significant positive correlation at high level (r = 0.74, p < 0.01). In addition, enabling others to act showed statistically significant positive at high level with nurse job - satisfaction, motivation factors and hygiene factors (r = 0.77, 0.73, 0.71, p < 0.01 respectively). The result indicates that head nurse should perform exemplary leadership in order to increase nurse job - satisfaction, especially enabling nurses to show their ability to advance in career path.